The System of Poetry Translation Strategies in Modern Translation Studies - HAMBARDZUMYAN, HAYK (Bulletin of Yerevan University B: Philology, 2021)
The aim of this article is to conduct a comprehensive analysis among pivotal theories and ideologies on poetry translation, outline the strategies effective in poetry translation and sum up the results with a hierarchical model based on faithfulness to the original text. The theories subjected to scrutiny in the article relate to translation studies, as well as interdisciplinary studies. A comparative analysis has been conducted, and the main theoretical directions have been pinpointed. The hierarchical model developed as a result of analyses is applicable as a framework for pre-translation analysis and a tool for translation evaluation.